An Examination of Transactional Law Clinics and Interdisciplinary Education - Dina Schlossberg (Washington University Journal of Law & Policy, 2003)
This Essay examines the notion of a transactional legal clinic designed around interdisciplinary education and service delivery. Part I explains why it is advantageous to both students and clients to design a transactional law clinic utilizing an interdisciplinary design. Part II explores the challenges involved in the creation and operation of such a clinical model. Part III describes examples of how other transactional law clinical programs explore interdisciplinary and integrative approaches in teaching and in serving clients. This Essay neither criticizes the current model of transactional law clinical programs, nor champions a universal change in clinic design. Rather, this Essay adds to the current body of literature on clinical education and critically examines the goals of teachers and lawyers who are engaged in the practice of transactional law.
Keywords: Clinical legal education; Interdisciplinary approach in education; Commercial law; Interdisciplinary approach (Education); United States